Doorframe of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The doorframe of the garbhagriha (sanctum sanctorum) has two floral shakhas (vertical bands or branches), a central dominant stambha shakha (pillar-shaped branch) with a purnaghata kalasha (vase and foliage), and an outer shakha adorned with vyalas (composite mythical creatures) arranged in a vertical chain.